2007
DOI: 10.1186/1475-2867-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Base excision repair of ionizing radiation-induced DNA damage in G1 and G2 cell cycle phases

Abstract: BackgroundMajor genomic surveillance mechanisms regulated in response to DNA damage exist at the G1/S and G2/M checkpoints. It is presumed that these delays provide time for the repair of damaged DNA. Cells have developed multiple DNA repair pathways to protect themselves from different types of DNA damage. Oxidative DNA damage is processed by the base excision repair (BER) pathway. Little is known about the BER of ionizing radiation-induced DNA damage and putative heterogeneity of BER in the cell cycle contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…We also note that recent studies have demonstrated a cell cycle or proliferation state dependence in the activity of some DNA repair proteins, including several in the BER pathway (47,48). However, our previous studies have established that although BRCA1 can contribute to stress-activated cell cycle checkpoints, neither overexpression (WTBRCA1) nor underexpression (BRCA1-siRNA) of BRCA1 significantly altered the in vitro growth rate or cell cycle distribution of established cancer cell lines grown under standard cell culture conditions (Dulbecco's modified Eagle's medium plus 5-10% fetal calf serum) (22,27,50).…”
Section: Discussionmentioning
confidence: 77%
“…We also note that recent studies have demonstrated a cell cycle or proliferation state dependence in the activity of some DNA repair proteins, including several in the BER pathway (47,48). However, our previous studies have established that although BRCA1 can contribute to stress-activated cell cycle checkpoints, neither overexpression (WTBRCA1) nor underexpression (BRCA1-siRNA) of BRCA1 significantly altered the in vitro growth rate or cell cycle distribution of established cancer cell lines grown under standard cell culture conditions (Dulbecco's modified Eagle's medium plus 5-10% fetal calf serum) (22,27,50).…”
Section: Discussionmentioning
confidence: 77%
“…Our measurements in these tissues will disproportionately reflect the activities of highly differ- Narciso et al (2007) demonstrated that a significant reduction in BER capacity occurs during differentiation of actively mitotic skeletal muscle progenitors (myoblasts) to post-mitotic myotubes (myofiber-like). Other authors have shown that BER enzyme activities are upregulated at specific times during the cell cycle (Chaudhry 2007) and are generally elevated in tissues containing higher proportions of actively mitotic cells (see Karahalil et al 2002). Perhaps the expected correlations of DNA repair activities with MLSP manifest in actively mitotic cells.…”
Section: Discussionmentioning
confidence: 96%
“…Treatment options for gliomas include surgical resection followed by chemotherapy with temozolomide (TMZ) or radiation, both of which generate lesions repaired by the BER pathway (Evans et al, 2000;Chaudhry, 2007;Stupp et al, 2007). These treatments rarely result in complete remission and are often accompanied by adverse toxic effects in longer surviving patients (Stupp et al, 2007).…”
Section: Introductionmentioning
confidence: 99%